#### Answer

x = 2.666666667

#### Work Step by Step

Simplifying
6x + -1 = 9x + -9
Reorder the terms:
-1 + 6x = 9x + -9
Reorder the terms:
-1 + 6x = -9 + 9x
Solving
-1 + 6x = -9 + 9x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-9x' to each side of the equation.
-1 + 6x + -9x = -9 + 9x + -9x
Combine like terms: 6x + -9x = -3x
-1 + -3x = -9 + 9x + -9x
Combine like terms: 9x + -9x = 0
-1 + -3x = -9 + 0
-1 + -3x = -9
Add '1' to each side of the equation.
-1 + 1 + -3x = -9 + 1
Combine like terms: -1 + 1 = 0
0 + -3x = -9 + 1
-3x = -9 + 1
Combine like terms: -9 + 1 = -8
-3x = -8
Divide each side by '-3'.
x = 2.666666667
Simplifying
x = 2.666666667